Effects of natural aging and gender on pro-inflammatory markers - Milan-Mattos,J.C. (2019)
The term inflammaging is now widely used to designate the inflammatory process of natural aging. During this process, cytokine balance is altered, presumably due to the loss of homeostasis, thus contributing to a greater predisposition to disease and exacerbation of chronic diseases. The aim of the study was to analyze the relationship between pro-inflammatory markers and age in the natural aging process of healthy individuals. One hundred and ten subjects were divided into 5 groups according to age (22 subjects/group). Interleukin-6 (IL-6) and tumor necrosis factor α (TNF-α) were quantified using the ELISA method. High-sensitivity C-reactive protein (hsCRP) was analyzed by turbidimetry according to laboratory procedures. The main findings of this study were: a positive correlation between hsCRP and IL-6 as a function of age (110 subjects); women showed stronger correlations; the 51–60 age group had the highest values for hsCRP and IL-6; women presented higher values for hsCRP in the 51–60 age group and higher values for IL-6 in the 61–70 age group; and men showed higher values in the 51–60 age group for hsCRP and IL-6. In conclusion, the natural aging process increased IL-6 and hsCRP levels, which is consistent with the inflammaging theory; however, women presented stronger correlations compared to men (IL-6 and hsCRP) and the 51–60 age range seems to be a key point for these increases. These findings are important because they indicate that early preventive measures may minimize the increase in these inflammatory markers in natural human aging.